1987
DOI: 10.1159/000184477
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy Associated with Hepatitis B Virus Antigenemia

Abstract: The pathogenetic ability of hepatitis B virus (HBV) antigenemia to induce IgA nephropathy was examined in 10 patients with IgA nephropathy and HBV antigenemia. They had no previous history of liver diseases and their liver function tests were normal. All were positive for hepatitis + surface antigen (HBsAg) and antibody to hepatitis B core antigen (anti-HBcAg) with high titers, thereby indicating they were persistent carriers of HBV. Immunoperoxidase studies using monospecific polyclonal antibodies revealed HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…HBV has long been known to be associated with a variety of glomerular diseases including membranous glomerulonephritis, membranoproliferative glomerulonephritis and mesangial proliferative glomerulonephritis (4-9). In addition, polyarteritis nodosa and immunoglobulin A nephropathy have also been associated with chronic HBV infection (10)(11)(12)(13). First described in 1971 by Combes et al (4), MGN is the most commonly associated renal disorder, with epidemiological studies subsequently confirming its association with HBV.…”
Section: Discussionmentioning
confidence: 99%
“…HBV has long been known to be associated with a variety of glomerular diseases including membranous glomerulonephritis, membranoproliferative glomerulonephritis and mesangial proliferative glomerulonephritis (4-9). In addition, polyarteritis nodosa and immunoglobulin A nephropathy have also been associated with chronic HBV infection (10)(11)(12)(13). First described in 1971 by Combes et al (4), MGN is the most commonly associated renal disorder, with epidemiological studies subsequently confirming its association with HBV.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] In addition, other authors have suggested IgA nephropathy to be associated with certain types of microorganisms. [22][23][24][25][26] In particular, deposits of Haemophilus parainfluenzae-related proteins have been demonstrated in kidney tissue specimens from Japanese patients with IgA nephropathy. Patients with IgA nephropathy have also been suggested to have significantly higher levels of IgA antibody specific to Haemophilus parainfluenzae than did patients with other glomerular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…All three major hepatitis B virus antigens, including HBsAg, HBeAg, and HBeAg, had been localized in glo merular capillary wall or measangium [7,8,12,[15][16][17], This could suggest a mechanism involving hepatitis B virus antigen containing immune complexes which result from passive trapping or local immune complex forma tion at this site. However, the presence of hepatitis B virus antigens in the glomerulus also could be a result of non specific passive trapping and not responsible for the glo merular lesion [3], Circulating immune complexes need to be very small and cationic to penetrate the basement membrane via the subepithelial space [18].…”
Section: H Epatitis B Virus Associated G Lom Erulonephrit Ismentioning
confidence: 99%